Analysis Of Soil Water Distribution By Low-Pressure Drip Irrigation - Dinna Afriyana; Ahmad Tusi; Oktafri - (The University of Lampung, 2012)
This study was carried out to determine the effect of low-pressure surface and sub-surface drip irrigation to soil wetting distribution pattern and emission uniformity. The experiment was conducted with gravity drip irrigation system and modified point sources drip-line with polyester (PE) cloth. The PE covered the drip-line with 1, 2, and layer and operation head was conducted by 0.5 m, 0.75 m, and 1 m. Evaluation of trickle irrigation system design were conducted by two treatment, surface and sub-surface, and slope of surface land were 0%, +2% and -2%. The results indicated that the experiment using 3 layers of PE cover was better with the highest coefficient of water distribution uniformity with the following specifications: q= 1.31/hour with 1m head operation. The uniformity of distribution in sub-unit of this design was 74.6%, the average of diameter of soil surface wetting was 34 cm, and water content ranged from 20% - 54%. The average of sub-surface soil wetting was 31 cm, with average water content ranging from 24% - 30% in 6,5 hours application of irrigation. These ranges were still between the field capacity and permanent wilting point from the soil sample in location of study. Keywords: Low-pressure drip irrigation, polyester cloth, soil wetting distribution, emission uniformity.